Girls don't have cooties - Krulik, Nancy E. (Krulik, Nancy E. Katie Kazoo, switcheroo, 2002)
Katie wants to go to Suzanne's sleepover party, but Jeremy wants her to ride the new roller coaster with him. Annoyed, Jeremy and the other boys decide that all girls have cooties. When Katie literally finds herself in Jeremy's shoes, she tries to reunite the boys and girls. Illustrations.